A Conceptual Framework for Synergizing Marketing and Environmental Innovations to Enhance Sustainable Business Performance in Malaysia’s Technology Sector - Chu-Hui Ng; Jeffrey S.S Cheah (AIBPM Publisher, 2025)
Sustainable business performance (SBP) has emerged as a critical concern in light of escalating environmental degradation and resource depletion, especially in developing economies. This conceptual study explores how the synergy between marketing innovation (MI) and environmental innovation (EI) can enhance SBP in Malaysia’s technology sector. Anchored in the Resource-Based View (RBV), the objective is to develop an integrated framework that positions these innovations as strategic organizational resources contributing to economic, environmental, and social performance. A systematic literature review (SLR) was conducted using peer-reviewed articles from 2015 to 2020, resulting in the selection of seven core studies from six high-impact journals. The analysis revealed a consistent emphasis on eco-innovation and a notable gap in MI in sustainability. The proposed framework highlights the complementary effects of marketing and EI in fostering competitive advantage and long-term value creation. This study offers theoretical contributions to innovation-sustainability discourse and practical implications for managers and policymakers striving to embed sustainability into organizational strategies. Future empirical research is encouraged to validate the framework and investigate the interaction of contextual variables such as market turbulence and organizational agility.